Endoscopic Endonasal Reconstruction of High-Flow Cerebrospinal Fluid Leak with Fascia Lata “Button” Graft and Nasoseptal Flap: Surgical Technique and Case Series - Khatiwala, Roshni V.; Shastri, Karthik S.; Peris-Celda, Maria; Kenning, Tyler; Pinheiro-Neto, Carlos D. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background The endoscopic endonasal approach (EEA) has become increasingly used for resection of skull base tumors in the sellar and suprasellar regions. A nasoseptal flap (NSF) is routinely used for anterior skull base reconstruction; however, there are numerous additional allografts and autografts being used in conjunction with the NSF. The role of perioperative cerebrospinal fluid (CSF) diversion is also unclear.Objective This study was aimed to analyze success of high-flow CSF leak repair during EEA procedures without use of CSF diversion through lumbar drainage.Methods A retrospective chart review of patients who had intraoperative high-flow CSF leak during EEA procedures at our institution between January 2013 and December 2017 was performed. CSF leaks were repaired with use of a fascia lata button graft and nasoseptal flap, without use of perioperative lumbar drains.Results A total of 38 patients were identified (10 male, 28 female). Patient BMIs ranged from 19.7 to 49 kg/m2 (median = 31 kg/m2), with 18 patients meeting criteria for obesity (BMI > 30 kg/m2) and 12 patients overweight (25 kg/m2 < BMI < 29.9 kg/m2). There was no incidence of postoperative CSF leak.Conclusion In our experience, the nasoseptal flap used in conjunction with the fascia lata button graft is a safe, effective and robust combination for cranial base reconstruction with high-flow intraoperative CSF leaks, without need for lumbar drains.
Keywords: high-flow cerebrospinal fluid leak; endoscopic endonasal approach; fascia lata button graft; nasoseptal flap; pituitary adenoma; meningioma; craniopharyngioma